Cross-cultural comparison of motor competence in children from Australia and Belgium - Bardid, Farid; Rudd, James R.; Lenoir, Matthieu; Polman, Remco; Barnett, Lisa M. (Frontiers in Psychology, 2015)
Motor competence in childhood is an important determinant of physical activity and physical fitness in later life. However, childhood competence levels in many countries are lower than desired. Due to the many motor skill instruments in use children’s motor competence across countries is rarely compared. The purpose of this study was to evaluate the motor competence of children from Australia and Belgium using the Körperkoordinationstest für Kinder (KTK). The sample consisted of 244 (43.4% boys) Belgian children and 252 (50.0% boys) Australian children, aged 6 to 8 years (Australian 7.6 ± 0.7 and Belgian 7.3 ± 0.9). MANCOVA for the motor scores showed a significant country effect (F = 14.61, p < 0.001). Belgian children scored higher on jumping sideways (F = 6.61, p = 0.01), moving sideways (F = 40.52, p < 0.001) and hopping for height (F = 8.28, p = 0.004) but not for balancing backwards (F = 2.64, p = 0.105). Moreover, a Chi squared test revealed significant differences between the Belgian and Australian score distribution with 21.3% Belgian and 39.3% Australian children scoring ‘below average’ (χ2 = 23.06, p < 0.001). The very low levels reported by Australian children may be the result of cultural differences in physical activity contexts such as physical education and active transport. When compared to normed scores, both samples scored significantly worse than children 40 years ago. The decline in children’s motor competence is a global issue, largely influenced by increasing sedentary behaviour and a decline in physical activity.